2020
DOI: 10.1016/j.gloenvcha.2020.102148
|View full text |Cite|
|
Sign up to set email alerts
|

Water borrowing is consistently practiced globally and is associated with water-related system failures across diverse environments

Abstract: Water problems due to scarcity, inaccessibility, or poor quality are a major barrier to household functioning, livelihood, and health globally. Household-to-household water borrowing has been posited as a strategy to alleviate unmet water needs. However, the prevalence and predictors of this practice have not been systematically examined. Therefore, we tested whether water borrowing occurs across diverse global contexts with varying water problems. Second, we tested if household water borrowing is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

6
4

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…If people cannot readily access community water supplies when physical distancing, water sharing between neighboring households might increase as a coping strategy ( Wutich et al, 2018 ); this common adaptation has been observed in many LMICs ( Rosinger et al, 2020 ). Increased sharing potentially brings people into greater direct physical contact with each other.…”
Section: Resultsmentioning
confidence: 99%
“…If people cannot readily access community water supplies when physical distancing, water sharing between neighboring households might increase as a coping strategy ( Wutich et al, 2018 ); this common adaptation has been observed in many LMICs ( Rosinger et al, 2020 ). Increased sharing potentially brings people into greater direct physical contact with each other.…”
Section: Resultsmentioning
confidence: 99%
“…Our results show how changes in water are central in local perceptions of change, driving multiple changes in other elements of the biocultural system. Many IPLC across the world face important constraints to their water security and sovereignty, driven by both geographic and climatic conditions, but also by socioeconomic and political arrangements (Alessa et al 2008;Fernández-Llamazares et al 2020;Rosinger et al 2020). Ongoing and predicted changes in climate, such as changes in rainfall and in river fluctuation regimes (Jiménez Cisneros et al 2014), will affect the dynamics, availability, and quality of water resources.…”
Section: Discussionmentioning
confidence: 99%
“…Several HWISE-RCN-affiliated studies have focused on how these new metrics are associated with water governance (Miller et al 2020), water sharing (Rosinger et al 2020), financial expenditures on water , injuries (Venkataramanan et al 2020), and self-reported health (Jepson et al 2021). Research on the measurement of water insecurity, however, has not fully considered how the HWISE scale varies within and across sites.…”
Section: Introductionmentioning
confidence: 99%